Teseo y Heracles, algo más que una amistad (Argos, 2025)
On Euripides’ Heracles, the Dorian hero kills his family in a fit of madness. Once he is aware of what he has done, he decides to commit suicide, but Theseus persuades him otherwise. Given the peculiarity of this tragedy –in comparison with others that raise the same subject– I will analyse the healing power of the word in Heracles’ recovery. I will focus on the influence of the sophist movement, particularly the figures of Protagoras and Gorgias in Euripides’ work since I consider that the condition to develop a cure using words is the study that the sophists do on the persuasive function of the lógos.